2023
DOI: 10.4037/ajcc2023593
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Psychological Distress in Family Caregivers of Critically Ill Patients: A Qualitative Study

Abstract: Background Family caregivers often experience psychological distress during a critical care hospitalization, potentially compromising their ability to function effectively in a supportive role. A better understanding of the sources of family caregiver distress is needed to inform strategies to mitigate its development and impact. Objective To explore sources of family caregiver psychological distress during a critical care ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
4
0
1
Order By: Relevance
“…Regardless of contextual factors, the findings indicate that patient’s agency was consistently low for conditions of paternalistic decision-making, wherein doctors solely bear decision responsibilities (Davies & Parker, 2022). In a study, Blok et al (2023) interviewed 40 family caregivers of patients undergoing life-assistive treatment. They found that ‘anxious family caregivers’ expressed distress due to ‘lack of information about health care system processes’ (Blok et al, 2023, p. 25).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Regardless of contextual factors, the findings indicate that patient’s agency was consistently low for conditions of paternalistic decision-making, wherein doctors solely bear decision responsibilities (Davies & Parker, 2022). In a study, Blok et al (2023) interviewed 40 family caregivers of patients undergoing life-assistive treatment. They found that ‘anxious family caregivers’ expressed distress due to ‘lack of information about health care system processes’ (Blok et al, 2023, p. 25).…”
Section: Discussionmentioning
confidence: 99%
“…In a study, Blok et al (2023) interviewed 40 family caregivers of patients undergoing life-assistive treatment. They found that ‘anxious family caregivers’ expressed distress due to ‘lack of information about health care system processes’ (Blok et al, 2023, p. 25). Similarly, those in borderline anxiety group reported that ‘not understanding the reasons for the medical team’s care decisions contributed to their distress’ (Blok et al, 2023, p. 26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Essa situação leva ao desgaste devido à sobrecarga gerada pelo estresse que envolve a hospitalização, podendo acarretar diversas implicações negativas para o acompanhante, já que ele participa intensamente da vida e do sofrimento do paciente por conta da doença e tratamento. Por conta disso, o acompanhante tende a renunciar à sua individualidade, sofrendo prejuízos em seu cotidiano, podendo inclusive adoecer e ter seu julgamento e sua capacidade de cuidar afetados (Block et al, 2023;Rocha et al, 2020;Bianchin et al, 2015;Delalibera et al, 2015;Monteiro & Lang, 2015).…”
Section: Introductionunclassified

O Cuidado Emocional De Familiares E Cuidadores De Pessoas Com Câncer No Hospital

Fabiane de Amorim Almeida,
Livia Helena Della Dea Parreira,
Aline de Barros Campanelli Lima
et al. 2023
NTQR